35x+1=36x-1

Simple and best practice solution for 35x+1=36x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 35x+1=36x-1 equation:


Simplifying
35x + 1 = 36x + -1

Reorder the terms:
1 + 35x = 36x + -1

Reorder the terms:
1 + 35x = -1 + 36x

Solving
1 + 35x = -1 + 36x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-36x' to each side of the equation.
1 + 35x + -36x = -1 + 36x + -36x

Combine like terms: 35x + -36x = -1x
1 + -1x = -1 + 36x + -36x

Combine like terms: 36x + -36x = 0
1 + -1x = -1 + 0
1 + -1x = -1

Add '-1' to each side of the equation.
1 + -1 + -1x = -1 + -1

Combine like terms: 1 + -1 = 0
0 + -1x = -1 + -1
-1x = -1 + -1

Combine like terms: -1 + -1 = -2
-1x = -2

Divide each side by '-1'.
x = 2

Simplifying
x = 2

See similar equations:

| -100/-20 | | 20x-8=18x+6 | | w^4-9w^2+8=0 | | (2x+7)4=124 | | B+2+3=7 | | 20x-2=18x+8 | | -3x+7=1-3x | | 0.7(x+9)=15 | | 20x+5=19x+11 | | -2x+13=.5x-20 | | 26d=520 | | 231+10x=18y+5 | | 6x^2+10=2x^2+30 | | m+-255=2 | | (7y+8)-(5+6y)=6 | | 20x-2=18x+6 | | -5=d/-29 | | 2g-14=2 | | 1-4n=-5n+1 | | m+-72=-43 | | [8x+4]=8 | | 16=r-25 | | -2+2m=m-5 | | 2.5x*x=250 | | 2(3x+4)=355 | | p/7=6 | | 10+x-3x=25 | | -5m+6=-8-7m | | 7j=-28 | | 2+3n-2=-9 | | (5/5x)-(4/5x)=(5x/5x) | | (x-5)+(x+35)+x+1.4=360 |

Equations solver categories